An Efficient Method for the Production of Biodiesel from Rice Bran - Siti Zullaikah; Yulia T. Rakhadima; M. Rachimoellah; Tri Widjaja; Sumarno Sumarno (IPTEK Journal of Proceedings Series, 2014)
A modified in situ esterification was employed for the economic competitiveness of biodiesel production from rice bran.  The effects of methanol to rice bran ratio, acid catalysts, and reaction time on the biodiesel yield and purity were investigated. Biodiesel yield and purity of 17.99% and 67.04%, respectively, were obtained used acid catalyst (H2SO4) of 2.37%, ratio of methanol and rice bran of 15 (mL/g), and 5 h of reaction time.  Recovery of crude biodiesel obtained was 92.45%. Based on the proposed method, the production process of biodiesel could be simplified and improved; therefore, the production cost probably could be reduced further.